Professional Pedagogy in Medical Universities: Training Competent Medical Workers - Juraeva Barno Gulamovna (European Science Publishing, 2024)
The field of medical education is at a crossroads, facing the dual challenges of maintaining high educational standards and adapting to rapid technological advances and the changing needs of society. Professional pedagogy in medical schools plays a key role in shaping the next generation of healthcare professionals, ensuring that they are not only knowledgeable, but also adaptable, empathetic and capable of delivering high-quality care. This article examines the evolution, current practice, and future directions of professional pedagogy in medical education, focusing on the integration of innovative teaching methodologies, interdisciplinary learning, and the development of a holistic professional identity among medical students.
Keywords: problem-based learning, evidence-based medicine, interprofessional education, medical educators, virtual reality (VR), artificial intelligence (AI)